Use of visual appearance as an indicator of degree of doneness in ground beef patties - Warren, K.E.; Hunt, Melvin C.; Hague, M.A.; Kropf, Donald H.; Stroda, Sally L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Outbreaks of food-borne illness have emphasized the need for proper cooking of ground beef patties. Because of difficulties in measuring internal temperature of ground beef patties, visual indicators usually are used to estimate degree of doneness. As internal temperature increases from 130 to 170 ̊F, the internal appearance is expected to change from very red to brown and juice color from red to clear. Based on ground beef patties from three sources, we found that internal color over-estimated internal temperature. Expressible juice decreased in redness as internal temperature increased but did not run clear even at temperatures over 160 ̊F. Regardless, expressible juice color was a better indicator of degree of doneness than internal color.
Keywords: Beef; Ground beef; Color; Cookery; End-point temperature; Safety